Perilaku Konsumen Muslim Generasi-Z Dalam Pengadopsian Dompet Digital - Nada Diva Rizki Rembulan; Egi Arvian Firmansyah (Sekolah Tinggi Ilmu Ekonomi AMM, 2020)
It has been two years since Indonesian consumers was introduced to a new payment system, named electronic wallet (E-wallet). In addition to its simplicity and are easy to use, E-wallets are also seemed to have many advantages with the addition of discounts and cashbacks that are offered. In this phenomenon of adopting new technology, it is obvious that there are many factors that affected it. The purpose of this study is to identify how the TAM (Technology Adoption Model) Theory and UTAUT (Unified Theory of Acceptance and Use of Tehnology), in addition to other related things, could influenced the consumers’s decision to use E-wallet. The PLS-SEM method and convenience sampling were used. 427 people, which consists of Gen-Z Muslims in all over Indonesia, participated in this study. The results showed that PEOU (Perceived Ease of Use), PU (Perceived Usefulness), FC (Facility Condition), TRST (Trust), SI (Social Influence) dan LC (Lifestyle Compatibility) significantly influenced E-wallet usage. Meanwhile, SCR (Security) influenced usage through TRST (Trust).